Governance Matters III : Governance Indicators for 1996, 1998, 2000, and 2002 - Kaufmann, Daniel; Kraay, Aart; Mastruzzi, Massimo (Washington, DC: World Bank, 2014)
This article presents estimates of six dimensions of governance for 199 countries and territories for 1996, 1998, 2000, and 2002 developed in the context of an ongoing project to measure governance across countries. Section one describes the data used in developing this round of the governance indicators, which include several new sources. Data sources used in the earlier studies were updated forward to 2002 and backward to 1996, and previously estimated indicators for 1998 and 2000were revised to reflect the new data. The aggregation procedure, described in section two, provides not only estimates of governance for each country but also measures of the precision or reliability of these estimates. Although the new data have improved the precision of the governance indicators, the margins of error remain large relative to the units in which governance is measured, so that comparisons across countries and especially over time should be made with caution.